The Applications of Next-generation Sequencing (NGS) in Drug Development for Cancer Therapy - Telkoparan-Akillilar, Pelin; Cevik, Dilek (Current Analytical Chemistry, 2021)
Background: Numerous sequencing techniques have been progressed since the 1960s with the rapid development of molecular biology studies focusing on DNA and RNA. Methods: A great number of articles, book chapters, websites are reviewed, and the studies covering NGS history, technology and applications to cancer therapy are included in the present article. Results: High throughput next-generation sequencing (NGS) technologies offer many advantages over classical Sanger sequencing with decreasing cost per base and increasing sequencing efficiency. NGS technologies are combined with bioinformatics software to sequence genomes to be used in diagnostics, transcriptomics, epidemiologic and clinical trials in biomedical sciences. NGS technology has also been successfully used in drug discovery for the treatment of different cancers. Conclusion: This review focuses on current and potential applications of NGS in various stages of drug discovery process, from target identification through to personalized medicine.
Keywords: drug discovery